Community Building, Original Event Programming, Convenience, and Connectivity for SMEs in Digital Branding Moderated by Digital Literacy - Sunandes, Aris; Sudarmiatin, Sudarmiatin; Rahayu, Wening Patmi (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze the influence of community development, the organization of original events, convenience, and connectivity on digital branding for micro, small, and medium enterprises (MSMEs) in Blitar, with an emphasis on the moderating role of digital literacy. The method used in this research is a quantitative approach with a Moderated Regression Analysis (MRA). The results show that community development and the organization of original events have a significant positive impact on digital branding, while convenience also plays a role in enhancing the effectiveness of digital branding. On the other hand, connectivity does not significantly influence digital branding. Digital literacy is proven to act as a moderator that strengthens the relationships between community development, event organization, and convenience with digital branding, highlighting the importance of digital skills in achieving successful branding. This study suggests that MSMEs in Blitar should pay greater attention to community development, creative events, and ease of digital services. Additionally, improving digital literacy among MSME owners and staff is crucial to optimize their digital branding efforts.